Hybrid formation and properties of rubber silicate nanocomposite - Navaja, Deorex David A. (2008)
This research aims to develop a nanocomposite of a recycled polymer embedded with layers of alumino-silicates to form Polymer Layered Silicate Nanocomposites (PLSN). The three-layered silicate of nanosized particles used in this study is montmorillonite, extracted from the bentonite deposit of Albay, Philippines. The raw clay was beneficiated, sodium activated and intercalated with quaternary alkylammonium cations to expand the lattice structures of montmorillonites. The polymer used was recycled Polyethylene Terephthalate (RPET) from post-consumer waste, reprocessed by EREMA Plastics Recycling Systems using the VACUREMA Technology. Different proportions of organically modified montmorillonites were dispersed in the RPET matrix using three (3) melt processing techniques of hybrid formation : melt intercalation by two roll mill, compression melt and twin screw extrusion melt methods.The effect of processing technique and clay loading on the structural, thermal and mechanical properties of the intercalated products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), small angle x-ray diffraction (SAXS), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and mechanical analysis. The difference of using recycled PET vis-à-vis virgin PET (VPET) as matrix in the polymer nanocomposites and the use of synthesized Philippine organoclay vis-à-vis commercial organoclay as the layered silicates, were evacuated. Based on Stoke?s Law, montmorillonite particles were liberated from its impurities (cristobalite, x-quartz and feldspar), resulting to an immense surface area and excellent adsorption capacity. Surface treatment chemistries by adding dimethyldiakyl ammonium chloride swelled the aggregates making it available for intercalation with polymers. The structural arrangement and orientation achieved monomolecular and paraffinic structures, giving the highest possible expansion of the layered silicate. The RPET resin produced by EREMA showed similar structural and chemical characteristics with VPET resin. However, the thermal behavior and mechanical properties differed. The final product after 2nd heating in the DSC analysis showed higher glass transition temperature (Tg) and lower melting temperature ? for RPET than VPET. This may be attributed to the difference in thermal and mechanical history before use. Moreover, VPET showed better mechanical properties than RPET. Varying the hybrid formation techniques produces different nanomorphologies in the developed PLSN. The melt intercalation methods using compression and twin screw extrusion gave generally exfoliated structures while using two roll mill gave laminated structures. However, localized laminated structures were observed in both the compression and extrusion methods. Clay loading at <5% was favorable to produce exfoliated structures using the twin screw extrusion melt method. Thermal degradation has been decreased and the tensile strength improved with the increase in clay loading. Philippine organoclay intercalated with VPET produced exfoliated structures even at higher clay loadings (10%), while RPET-PHIL systems indicated partially oriented structures at >5% loadings. Generally, favorable enthalphy of mixing the PET (RPET or VPET) with organoclays (PHIL or FLUKA) was achieved. Four (4) phenomenological models were developed to describe the structure property relationships of the organic inorganic hybrids. The objective of this research is to synthesize a nanocomposite of rubber embedded with nano-sized layers of alumino-silicates to form a rubber silicate nanocomposite. The interaction on how the layered silicate influences the properties of this nanocomposite in terms of its mechanical, thermal and structural behaviors is likewise investigated. The layered-silicate nanoclays (montmorillonite) were extracted from a local bentonite ore sample using sedimentation method. By ion-exchange reaction, the natural calcium montmorillonite (Ca-MMT) particles were converted to sodium montmorillonite (Na-MMT) which resulted in the swelling of its silicate layers. Surface treatment of Na-MMT by the addition of quaternary alkylammonium salt resulted in the expansion of lamellar aggregates. This makes the silicate layers available for intercalation with natural rubber thus creating predominantly exfoliated structures in the rubber matrix. Hybrid formation technique by two roll mill melt intercalation process was used to disperse different proportions of organically modified montmorillonite in the synthesis of rubber silicate nanocomposite. The effective role of nanoclay filler to the property enhancement of rubber compound was investigated. The results of this study showed that the addition of nanoclay to the natural rubber matrix produced an effective polymer nanocomposite by the intercalation of macromolecules into the interlayer spaces of clay. Low concentration of nanoclay filler, 5 phr (per hundred rubber), significantly improved the tensile strength, coefficient of thermal expansion, thermal stability, and dimensional stability of the resulting rubber silicate nanocomposite compared with the imported rubber carbon composite. The developed rubber silicate nanocomposites using natural rubber and locally synthesized nanoclay showed potential economic and technological advantages that will support the growing local rubber and mining industries.
"April 2008."
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman.
Keywords: Nanostructured materials; Polymeric composites; Montmorillonite; Rubber, Artificial